Evaluation of Respiratory Symptoms, Spirometric Lung Patterns and Metal Fume Concentrations among Welders in Indoor Air-Conditioned Building at Malaysia - Zainal Bakri, Siti Farhana; Hariri, Azian; Ismail, Marzuki; Abdullah, Samsuri; Kassim, Nazrul Idzham (International Journal of Integrated Engineering, 2018)
Welding is one of the fundamental processes for metal joining in automotive industries and there is an increasing concern over occupational lung disease among welder due to exposure towards welding fumes. A lung disease questionnaire (ATS-DLD-78) was used to record the presence of respiratory symptoms among welders and in assessing lung function assessment, FEV1, FVC and FEV1/FVC are considered for identifying the lung condition; normal, obstructive or restrictive. The data were tabulated and subjected to logistic and multivariate analyses. Meanwhile, in order to trace metal in welders’ body, this study utilized a non-invasive approach of toenail as a biomarker. Lung functions decrement was established in linear regression for FEV1 and FEV1/FVC respectively although not statistically significant. Analysis conducted revealed the presence of the following trace elements concentration in ascending sequence: As < Al < Cu < Mn < Cr < Ni < Co < Fe (in the toenail) and Co < Al < Cu < Ni < As < Cr < Fe < Mn (in the cassette), respectively. The results validated the postulation that toenail metals composition shared a similar route of exposure with an anthropogenic source of activity. It is suggested a longer follow-up study is required to assess individual effects on lung function systems and the incidence of respiratory diseases among welders and this study indicates that toenail is a reliable biomarker of metal-workplace pollution and suitable for acquiring chronological information of welding fumes exposure.